Ankle Fracture Osteosynthesis Evaluation of Functional and Radiological Outcome by Baird and Jackson Scoring System - Komal P Gola; Santhosh K G; Surendher K (Journal of Orthopedics and Joint Surgery)
Introduction: Ankle fractures account for 10% of all fractures and are the most common lower limb injuries encountered by orthopedicians, with an incidence of 137/lakh/year. Improperly treated fractures result in long-term pain, instability, secondary arthritis, psychological, and social consequences. Therefore, a proper understanding of anatomy, mechanism of injury, radiographic interpretation forms the basis of a good outcome. Fractures treated with open reduction and internal fixation (ORIF) using the AO principles will have a good functional and radiological outcome. This study aimed to evaluate the ankle fractures treated with ORIF by Baird and Jackson scoring system. Material and methods: In this prospective study, 30 patients were classified according to Lauge-Hansen classification and underwent ORIF following AO principles from January 2019 to May 2020. Each patient was followed up for 6 months and an assessment of the outcome was done. Results: Out of 30 patients treated, overall excellent to good outcomes were obtained in 18 patients. The results were fair in six and poor in six patients. No statistical significance was noted between age, sex, mode of injury, and different method of fixation with regard to functional outcome. ORIF 48 hours after injury led to clinically significant outcomes. Overall, the meantime of the fracture union was 11.13 weeks. Statistical significance was seen in functional outcomes with regard to fracture union with a p-value of 0.001. Three patients developed complications in our study, surgical site infection in two patients and hardware irritation in one patient. Conclusion: Anatomical reduction and stable fixation are essential to maintain articular congruity in weight-bearing joints like the ankle. Short-term delay in surgery gave a favorable outcome in our series. Earlier the fracture union better the functional outcome.